Copper Complexes of the Tetradentate N, N′‐Bis(2‐amino‐3, 5‐di‐tert‐butylphenyl)‐2, 2′‐diaminobiphenyl Ligand. Issue 15 (9th April 2021) - Leconte, Nicolas; Berthiol, Florian; Philouze, Christian; Thomas, Fabrice
Abstract: The ligand N, N′‐ bis(2‐amino‐3, 5‐di‐ tert ‐butylphenyl)‐2, 2′‐diaminobiphenyl was synthesized and coordinated to copper. Complex 1 + was structurally characterized, showing two deprotonated diiminobenzoquinone ligands coordinated to a single Cu(I) center. The paramagnetic complexes 1 and 1 2+ were generated and characterized by EPR and Vis‐NIR spectroscopy. Complex 1 exhibits an isotropic resonance at g=2.00, which is reminiscent of Cu(I) diiminosemiquinone species. The dication 1 2+ exhibits a metal‐based ground spin state and hence is described as a Cu(II) diiminobenzoquinone complex. Both 1 and 1 + show a NIR band (954, 980 nm) of high intensity (>20 mM −1 cm −1 ) assigned to ligand‐based charge transfer transitions. Abstract : Complex 1 + (SbF6 − ) features two coordinated diiminobenzoquinone moieties. The copper(I) ion lies in a tetrahedrally distorded geometry and is air stable. Both the ligand and metal are redox‐active (in reduction and oxidation, respectively).This mononuclear complex catalyzes the aerobic oxidation of alcohols to aldehydes.